PENGARUH PROMOSI, HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE VIVO PADA MASYARAKAT KOTA YOGYAKARTA - Prawira, Endy Yudha; Sukardi, Sukardi (Universitas Ahmad Dahlan, 2019)
This study aims to determine the effect of promotion, price, and product quality for Smartphone purchase decisions VIVO The population of this research is the consumers of the city community Yogyakarta which is more than 17 years old and has already been make purchases of VIVO Smartphone products and samples used as many as 95 consumers in Yogyakarta, community engineering Sampling in this study is Purposive Sampling. The data analysis tool used is a linear regression test multiple. The results of this study indicate that promotions and Product quality has a significant effect on purchasing decisions while the price does not significantly influence the decision purchase. Simultaneously promotion, price, and quality variables significant effect on purchasing decisions. Promotion factor, price, and product quality affect purchasing decisions of 24.1% while the remaining 75.9% is influenced by Other variables that are not present in this study. Researchers expected can test variables other than product promotion, price, and quality to make a purchase decision.